Brief evolutionary development of the credit-module system and some issues of the gradual transition of the military education process in Uzbekistan to the credit-module system - Sotvoldiev Abdulhoshim Yuldashovich; Yuldashev Shukrullo (Genius Journals, 2021)
This article provides information on the brief evolutionary development of the creditmodule system and some issues of improving the quality of military education with the gradual transition of the military education process to the credit-module system in the universities of the Republic of Uzbekistan. The content of the article is methodologically successful on the structure of the educational program, planning and monitoring of military education, as well as the stages of planning the process of military education. The article is intended for the leadership of the Faculty of Military Education and faculty of higher education institutions, as well as for employees whose activities are related to military education
Keywords: Educational Program; Planning And Monitoring; Military Education; Credit-Module System